Magmatic or Not Magmatic? The 2015–2016 Seismic Swarm at the Long-Dormant Jailolo Volcano, West Halmahera, Indonesia - Passarelli, Luigi; Heryandoko, Nova; Cesca, Simone; Rivalta, Eleonora; Rasmid,; Rohadi, Supriyanto; Dahm, Torsten; Milkereit, Claus (Frontiers in Earth Science, 2018)
Seismic swarms close to volcanoes often signal the onset of unrest. Establishing whether magma is the culprit and the unrest can be flagged as magmatic may be challenging. Here we analyze the spatio-temporal pattern of a seismic swarm that occurred in November 2015 – February 2016 around Jailolo volcano, a long-dormant and poorly studied volcano located on Halmahera island, North Moluccas, Indonesia. The swarm included four Mw>5 earthquakes and hundreds of events were felt by the population. We relocate the earthquakes using both the Indonesian Seismic Network and single-station location techniques. We find that the earthquakes cluster in a narrow strip, stretching 5 km E–W and 20 km N–S, migrating southward away from Jailolo volcano at ~10 km/d. We investigate the source mechanisms of the largest earthquakes via full moment tensor inversion. The non-double-couple component is around 50%, such that the earthquakes, besides normal faulting, included a relatively large opening component. After a thorough examination of the possible causes of the Jailolo swarm we conclude that a laterally propagating dike of tens of millions of cubic meters is the triggering mechanism for the seismicity. The swarm marks the first documented magmatic unrest at Jailolo. We find that there is a probability >0.1 that the unrest will last for more than two years. This magmatic unrest calls for the classification of Jailolo volcano as active, and for an urgent assessment of the associated volcanic hazard.